Lack of association of somatic CAG repeat expansion with striatal neurodegeneration in HD knock-in animal models. Issue 16 (5th May 2021) - Bai, Dazhang; Yin, Peng; Zhang, Yiran; Sun, Fengwei; Chen, Laiqiang; Lin, Li; Yan, Sen; Li, Shihua; Li, Xiao-Jiang
Abstract: Our previous work has established a huntingtin knock-in (KI) pig model that displays striatal neuronal loss, allowing us to examine if somatic CAG expansion in striatum accounts for the preferential neurodegeneration in Huntington disease (HD). We found that HD KI pigs do not display somatic CAG expansion in striatum as HD KI mice and that the majority of polyQ repeats in exon 1 HTT in the striatum of HD KI mice are fairly stable. We also found that striatal MSH2 and MLH3, which are involved in DNA repair, are more abundant in mouse brains than pig brains. Consistently inhibiting MSH2 and MLH3 reduced the somatic CAG expansion in HD KI mouse striatum with no influence on neuropathology. Our findings suggest that somatic CAG expansion is species-dependent, occurs in a small fraction of the HD gene in mice, and does not critically contribute to HD neuropathology.